Spike destabilization attenuates Mink Cluster 5 SARS-CoV-2 - Julia N. Faraone; Pei Li; Junping Hong; Jinkai Zang; Yajie Liu; Yan Xu; Panke Qu; John P. Evans; Jie Chen; Yi-Min Zheng; Phylip Chen; Mark E. Peeples; et al. (Proceedings of the National Academy of Sciences, 2026)
Throughout the COVID-19 pandemic, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has shown the capacity to infect a wide range of nonhuman hosts, including farmed mink. In early 2020, a mink-associated variant, termed mink cluster 5 (MC5V), emerged in Denmark and spread to mink farmers and their household contacts but failed to cause a sustained outbreak and eventually disappeared. Here, we demonstrate that the spike protein (S) of MC5V is intrinsically unstable and impaired in processing, leading to markedly attenuated infectivity and fusogenicity. Remarkably, these defects are primarily driven by a single mutation, I692V, located in the S2 subunit of S, with additional contribution from the Y453F substitution in the receptor-binding domain. Structural analyses indicate that I692V induces conformational instability in S, promoting spontaneous S1 shedding and impairing spike incorporation into virions. These findings reveal that spike instability constrains viral fitness and emphasize the importance of monitoring zoonotic SARS-CoV-2 variants and other emerging viral pathogens.